Needing to Acquire a Physical Impairment/Disability: (Re)Thinking the Connections between Trans and Disability Studies through Transability. (8th September 2014) - Baril, Alexandre; Leblanc, Catriona
<x xml:space="preserve">Abstract</x> This article discusses the acquisition of a physical impairment/disability through voluntary body modification, or transability. From the perspectives of critical genealogy and feminist intersectional analysis, the article considers the ability and cis*/trans* axes in order to question the boundaries between trans and transabled experience and examines two assumptions impeding the conceptualization of their placement on the same continuum: 1) trans studies assumes an able‐bodied trans identity and able‐bodied trans subject of analysis; and 2) disability studies assumes a cis* disabled identity. The perception of transsexuality and transability as mutually exclusive phenomena results from a nonintersectional analysis of transsexuality as an issue of sex/gender, but not of ability, and of transability as an issue of ability, but not of sex/gender. Difficulty recognizing continuities between these phenomena thus stems from an ableist interpretation of sex/gender and a cis(gender)normative* interpretation of ability. This article aims to: 1) enrich intersectional analysis in trans and disability studies and transability scholarship; 2) complicate disability studies, in which disabilities are often presumed to be "involuntary, " and encourage the decentering of a cis* subject; 3) encourage trans studies to decenter an able‐bodied subject; and 4) advocate for increased dialogue and the creation of alliances between trans and disability studies and movements.